2012
DOI: 10.1364/oe.20.00a205
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of surface plasmons in organic light-emitting diodes via high-index coupling

Abstract: The efficiency of organic light-emitting diodes (OLEDs) is still limited by poor light outcoupling. In particular, the excitation of surface plasmon polaritons (SPPs) at metal-organic interfaces represents a major loss channel. By combining optical simulations and experiments on simplified luminescent thin-film structures we elaborate the conditions for the extraction of SPPs via coupling to high-index media. As a proof-of-concept, we demonstrate the possibility to extract light from wave-guided modes and surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Without going into the details (see, e.g., Ref. 99), it is clear from the figure that only for thin Alq 3 layers (up to about 50 nm) ordinary glass can be used to extract SPPs. For larger organic layer thickness, and in particular for the thicknesses typically used in OLEDs, the extraction of SPPs (in addition to waveguided modes that can also be extracted by this method) requires a medium on the top‐side of the metal that has a significantly higher refractive index.…”
Section: Approaches To Improved Light Outcouplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Without going into the details (see, e.g., Ref. 99), it is clear from the figure that only for thin Alq 3 layers (up to about 50 nm) ordinary glass can be used to extract SPPs. For larger organic layer thickness, and in particular for the thicknesses typically used in OLEDs, the extraction of SPPs (in addition to waveguided modes that can also be extracted by this method) requires a medium on the top‐side of the metal that has a significantly higher refractive index.…”
Section: Approaches To Improved Light Outcouplingmentioning
confidence: 99%
“…Also shown is the simulated angular dispersion of the modes that can be extracted through a fused silica prism as a function of the organic layer thickness: (e) p‐polarized, (f) s‐polarized (see also Refs. 94, 99).…”
Section: Approaches To Improved Light Outcouplingmentioning
confidence: 99%
“…To extract the remaining power lost into SPP excitations, scattering approaches have been proposed 20,24,25 , or methods involving complex microlens structures of high refractive index. 20,25,26 Here, we propose a method to increase the outcoupling efficiency η out of OLEDs by modifying the properties of the SPP excitations of the simple planar oparXiv:1503.01309v1 [physics.optics] 4 Mar 2015 tical cavity. We avoid power dissipation into evanescent modes by using Poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) as doped organic charge transport materials with a low refractive index.…”
Section: 3-5mentioning
confidence: 99%
“…Previous studies have shown that η OC of conventional OLEDs is limited at about 20% because total reflection at internal interfaces that light incidents from high refractive index medium to low refractive index medium 11‐13 . The η OC of OLEDs with various light‐out‐coupling (LOC) layers has been already reported 14‐25 . But there is still room for improvement because the η OC of OLEDs is only 30–50%.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The η OC of OLEDs with various light-out-coupling (LOC) layers has been already reported. [14][15][16][17][18][19][20][21][22][23][24][25] But there is still room for improvement because the η OC of OLEDs is only 30-50%. Simulation methods for the design of a white OLED (WOLED) structure with a LOC layer are indispensable to improve η OC .…”
Section: Introductionmentioning
confidence: 99%